Fungal Infection of Paranasal Sinus After COVID-19 Infection: A Tale of Two Fungi - Jangla, Sunayana Mukesh; Wadawkar, Atul Shivaji; Randive, Aniruddha Jayavant; Sakpal, Sandip Sakharam (Annals of Pathology and Laboratory Medicine, 2021)
Coronavirus disease (COVID-19) is an infection caused by Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2). Many twists and turns have occurred regarding its various aspects since the time it was first detected especially medical management. The COVID-19 symptom array has been ever expanding and recently secondary fungal infection has emerged as a top-up to the trouble. Post COVID-19 secondary fungal infections caused by Mucor have recently emerged as a cause of concern. However, infection caused by a combination of two fungal moulds from a site barring the lungs as a sequalae to the coronavirus disease comes as a surprise.